Functional performance of patients with stroke during inpatient rehabilitation: a cross-sectional study of home and access visits - Melissa J. Krauss; Emily Somerville; Callista Poiter; Rebecca M. Bollinger; Brianna M. Holden; Gabrielle Blenden; Danielle Kretzer; Susan L. Stark (BMC Health Services Research)
Abstract Background Home visits prior to inpatient rehabilitation facility (IRF) discharge allow occupational therapists to observe functional abilities among patients with stroke and address barriers that impact daily activities at home. However, home visits prior to IRF discharge are not standard practice due to barriers of time and cost constraints. We explored whether an access visit (visiting the home without the patient) could serve as an alternative to a home visit (with the patient) to anticipate functional abilities at home. Methods We used baseline data from a randomized controlled trial that occurred before and during the COVID-19 pandemic, which caused predischarge home visits to be modified to access visits without the participant. Participants had suffered a stroke and were treated in an IRF, aged ≥ 50, with plans to discharge home. International Classification of Functioning, Disability, and Health (ICF) qualifier scores were compared between participants’ home/access visits and IRF discharge. ICF scores were compared between predischarge home visits and IRF discharge and between access visits and IRF discharge using Wilcoxon signed-rank tests. Differences in ICF scores between home/access and IRF discharge were compared between home and access visits using linear regression models. Results Among 99 participants (58% men, average 67 years old, 60% Black), 57 received a home visit and 42 received an access visit. Both groups had significantly worse ICF scores at the home/access visit compared to IRF discharge for most activities. Differences in scores between home visit and IRF were significantly greater than between access and IRF for bathing, upper and lower body dressing, bed/chair transfer, walking, and navigating stairs. The largest differences between home and access visits were for walking (β = 1.05 95% CI 0.46 to 1.64) and going up and down stairs (β = 0.87 95% CI 0.25 to 1.49). Conclusions Participants with stroke had greater difficulty performing daily activities in both home and access visits than at the IRF, but observed differences were greater for home visits than access visits. While access visits may be beneficial to anticipate functional abilities in the home when home visits cannot occur, visiting the home to directly observe patients’ performance is ideal. Trial registration Registered on 3/26/2018 at clinicaltrials.gov, NCT03485820.